PERSEPSI AKUNTAN PENDIDIK, AKUNTAN PUBLIK, DAN MAHASISWA AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA - Muhdin Muhdin; Abdul Wahid Mahsuni; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT In Indonesia there have been cases of violations of the code of ethics carried out by an accountant profession, such as cases of violations of the ethics code at Ernst and Young's (EY) Partner Public Accountant Office in Indonesia, namely KAP Purwantono, Suherman and Sarja agreed to bring a US $ 1 Million fine (Approximately Rp. 13.3 billion) to US regulators, as a result of being convicted of auditing their clients' financial statements. The agreement was announced by the Public Company Accounting Oversight (PCAOB) Supervisory Agency on Thursday, February 9, 2017, Washington time. Therefore the researcher aims to find out how their views or perceptions of the professional code of ethics and whether there are significant differences between the accountant educator, public accountant, and accounting student towards the code of ethics of Indonesian accountant bonds located in Malang City, East Java. This study uses quantitative methods and the types of data used are primary data (Primary Data). Primary data is data that takes directly from data sources or research locations.Based on the results of the questionnaire distribution, then tested with One Way ANOVA, validity test, reliability test, normality test and homogeneity test. The results of this study indicate that there is a significant difference in research between accountant educators, public accountants, and accounting students towards the code of ethics of Indonesian accountant ties.Keywords: Perception, accounting profession, code of ethics